THE INTEGRATION OF ISLAMIC EDUCATION AND MULTICULTURAL EDUCATION IN INDONESIA - Ali Miftakhu Rosyad (al-Afkar, Journal For Islamic Studies, 2020)
The article aims to analyze an overview of Islamic education and multicultural education in Indonesian country. Multicultural education is not new concept in Indonesia, but it has been run as long as national education system. Both Islamic education and multicultural education are the way to prepare students to become good Muslim and good citizen. Teacher today must socialize and inculcate Islamic values and multicultural values as early as possible from elementary school. Junior high school, and senior highs school. Indonesia is the largest Muslim people country in the world. In modern era, some scholars have studied on Islamic education and multicultural education in the terms of philosophy, methodology and objective to be achieved. This study addressed multicultural phenomenon and Islamic education curriculum today in Indonesia. It provides for reader, researcher, and those who are involved in future studies of Indonesian country.